2016
DOI: 10.1111/wvn.12156
|View full text |Cite
|
Sign up to set email alerts
|

Effective Weight Loss for Children: A Meta‐analysis of Intervention Studies 2002–2015

Abstract: Background: Investigators have implemented a variety of strategies for managing and treating childhood overweight and obesity over the past decade, yet the high prevalence of childhood overweight or obesity remains. The aim of this meta-analysis was to examine the effectiveness of childhood overweight or obesity interventions addressing weight loss from 2002-September 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
2
14
0
3
Order By: Relevance
“…The reference lists of the remaining 45 meta‐analyses were scanned and another six meta‐analyses were added to the data set. This resulted in a collection of 51 meta‐analyses , of which relevant information was extracted using the PICOC method.…”
Section: Resultsmentioning
confidence: 99%
“…The reference lists of the remaining 45 meta‐analyses were scanned and another six meta‐analyses were added to the data set. This resulted in a collection of 51 meta‐analyses , of which relevant information was extracted using the PICOC method.…”
Section: Resultsmentioning
confidence: 99%
“…In this manner, ENTREN‐F was designed to work on family environment and communication and was administered separately in six 2‐hr sessions to parents and nine 2‐hr sessions to their children, with a further three 2‐hr sessions attended by both families and children (see Appendix B). The rationale to develop content for the parallel six parent sessions was based on the following reason: Parental degree of motivation is the key factor for child obesity intervention dropout (Braet et al, ; Gunnarsdottir et al, ), and thus, intervention motivation must be addressed to achieve a greater effectiveness of the promotion of healthy life habits (Snethen et al, ; Wilfley et al, ) and greater stability of the changes (Quattrin & Wilfley, ). Content and new material have been developed on the basis of the techniques of motivational interviewing (Miller & Rollnick, ) and models on educational styles, which concluded that there were four: responsible (democratic), authoritarian, permissive, and negligent (Maccoby & Martin, ).…”
Section: Entren‐f Interventionmentioning
confidence: 99%
“…Although the scientific community has strived to develop effective treatments for childhood obesity (Epstein, Paluch, Roemmich, & Beecher, ; Snethen, Broome, Treisman, Castro, & Kelber, ), there is clear evidence of the difficulty in obtaining moderate results beyond a slight weight loss (Knop et al, ; Skjåkødegård et al, 2014). These results tend to worsen throughout the adolescent stage and with increasing severity of the obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Snethen et al . ). Parents are considered very important to intervention‐related lifestyle changes, as they are responsible for the child's eating habits and physical environment and, ultimately, behaviours.…”
Section: Introductionmentioning
confidence: 97%